DETERMINATION OF END-ADSORBED POLYMER DENSITY PROFILES BY NEUTRON REFLECTOMETRY - Field, J; Toprakcioglu, C; Ball, R; Stanley, H; Dai, L; Barford, W; Penfold, J; Smith, G; Hamilton, W (1992)
Specular neutron reflection was used to investigate the density profile of polystyrene-poly-(ethylene oxide) (PS-PEO) block copolymers adsorbed from d-toluene onto quartz. The neutron beam passed through the quartz substrate and was reflected from the quartz/d-toluene interface. The PEO block, which comprises a small fraction of the total polymer molecular weight, strongly adsorbs onto the quartz substrate, while the PS block remains in solution. Thus, the chains form a terminally attached polymer 'brush'. The reflectivity profiles are well described by a parabolic or error function polymer density profile normal to the interface, but the data cannot be fitted to exponential or power law decay profiles. The layer thickness values are in good agreement with the results of interlayer force measurements for the same polymer-solvent system adsorbing onto mica. The molecular weight dependence of the layer thickness and adsorbance obtained from the data obey scaling laws in accord with the theory of semidilute polymer brushes.